Korean red ginseng extract prevents bone loss in an oral model of glucocorticoid induced osteoporosis in mice - Chargo, Nicholas J.; Kang, Ho Jun; Das, Subhashari; Jin, Yining; Rockwell, Cheryl; Cho, Jae Youl; McCabe, Laura R.; Parameswaran, Narayanan (Frontiers in Pharmacology, 2024)
The gut microbiota and barrier function play important roles in bone health. We previously demonstrated that chronic glucocorticoid (GC)-induced bone loss in mice is associated with significant shifts in gut microbiota composition and impaired gut barrier function. Korean Red Ginseng (KRG, Panax Ginseng Meyer, Araliaceae) extract has been shown to prevent Glucocorticoid-induced osteoporosis (GIO) in a subcutaneous pellet model in mice, but its effect on gut microbiota and barrier function in this context is not known. The overall goal of this study was to test the effect of KRG extract in a clinically relevant, oral model of GIO and further investigate its role in modulating the gut-bone axis. Growing male mice (CD-1, 8 weeks) were treated with 75 g/mL corticosterone (~9 mg/kg/day) or 0.4% ethanol vehicle in the drinking water for 4 weeks. During this 4-week period, mice were treated daily with 500 mg/kg/day KRG extract dissolved in sterile water or an equal amount of sterile water via oral gastric gavage. After 4 weeks of treatment, we assessed bone volume, microbiota composition, gut barrier integrity, and immune cells in the bone marrow (BM) and mesenteric lymph nodes (MLN). Four weeks of oral GC treatment caused significant distal femur trabecular bone loss, and this was associated with changes in gut microbiota composition, impaired gut barrier function and altered immune cell composition. Importantly, KRG extract prevented distal femur trabecular bone loss and caused significant alterations in gut microbiota composition but had only modest effects on gut barrier function and immune cell populations. Taken together, these results demonstrate that KRG extract significantly modulates the gut microbiota-bone axis and prevents glucocorticoid-induced bone loss in mice.